The Teaching of Skills in Undergraduate Studies: Application case: Title of Leadership of the San Pablo CEU University - Martín Gómez, Sonia; Bartolomé Muñoz de Luna, Ángel; Lago Ávila, María Jesús (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This article describes an educational innovation project for learning skills, carried out in the Own Leadership Course of the San Pablo CEU University, transversal to all its educational offer. This is a new project based on hybrid teaching, where the more theoretical masterclasses have been complemented with a challenge-based learning linked to communication and sustainability matters, applying the Design Sprint methodology. In this way, the student is trained in the so-called soft skills that are increasingly in demand by the work environment.